COLOUR DESIGNATION COMPONENT AS A MEANS OF REFLECTING THE SELF-CONSCIOUSNESS - Tukhtayeva, Nilufar (Журнал иностранных языков и лингвистики, 2021)
COLOUR DESIGNATION COMPONENT AS A MEANS OF REFLECTING THE SELF-CONSCIOUSNESS